The model to optimize deliveries of perishable food products in supply chains - Vorkut, Tetiana; Volynets, Lyudmila; Bilonog, Okcana; Sopotsko, Olga; Levchenko, Iaroslava (Eastern-European Journal of Enterprise Technologies, 2019)
The probabilistic-statistical analytical model of optimizing the supply of perishable food products (PFPs) has been improved. The demand for PFPs is effectively satisfied by introducing into supply chain systems a possibility for additional delivery of PFPs in case of their deficit in the period between planned deliveries. It has been proven that the optimum size of basic delivery that corresponds to the maximum profit of a PFP supply chain system is affected by the following: – the magnitude of profit from the sale of a single PFP unit earned from basic and additional delivery; – the magnitude of loss incurred due to excess PFP units; – the parameters of demand distribution between the periods of planned deliveries; – technical-operational and economic indicators that characterize the operation of automobiles along multi-drop routes. We have performed a comparative analysis of conditions for ensuring PFP deliveries in supply chain systems using the known and proposed improved variant of the probabilistic-statistical analytical model of PFP deliveries optimization. This analysis has revealed that the two-stage supply system, that is the one that implies additional delivery, is more economical-reasonable in terms of conditions for the operation of PFP supply chains. The expedience of increasing transportation expenditures related to transporting additional deliveries has been proven. It is their increase that predetermines a significant increase in the system’s profit by achieving a high level of demand satisfaction and reducing losses incurred through the formation of unsold excess products